(untitled) (International Journal of Food and Nutritional Sciences, 2021)
All the business houses are part and parcel of the society. Their survival of business is depends upon stakeholders support. Managers are discovering that maximization of return to stockholders is not a sufficient goal, society is demanding more and making demands stick through legislation, litigation and public presser. Corporations are being told, ‘’ your job is to serve society through reliable and safe products and of high quality and were expect you to be good citizen while you are about it—no pollution, no discrimination, no hazardous working conditions etc. Considering this point of view there is responsibility of business towards society is to work for minimise social issues. This concept is also based on ethical issue but there was not legal frame work regarding how to define social responsibility. Corporate Social Responsibility is a management concept whereby companies integrate social and environmental concerns in their business operations and interactions with their stakeholders. The purpose of this study is to identify regional allocation and utilisation of CSR fund in Maharashtra. Rather than that the study explore the information regarding various corporate houses current CSR practices in India. This paper examines companies view, and conducts their CSR practices on environmental issues, responsible sourcing, stakeholder engagement, development of labour standards and working conditions, employee and community relations, social equity, gender balance, human rights, etc.